Sense of Community dan Fragmentasi Identitas Diaspora Muslim Indonesia: Studi Kasus AIMF-ACT dan IMCV di Australia - Rizqa Ahmadi; Muhammad Muntahibun Nafis (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
The Indonesian Muslim diaspora maintains both social and Islamic identities in their host countries. In this context, numerous studies indicate that the quest for identity generates divisions among Muslims and might, to some degree, incite disputes and rivalries. This article contradicts that assertion. We collected data during a participatory experience in community service activities grounded in Assets-Based Community Development (ABCD) at two Indonesian Muslim organizations in Australia, specifically AIMF-ACT and IMCV. This article, utilizing the qualitative case study technique, reveals that members of both organizations possess a dynamic sense of community. Amidst the diversity of identities present in each individual, a sense of unity emerges. The sense of community derives from geographical linkages and a collective commitment to the significance of practicing Islam within a diverse context. Although not all members realize it, awareness of the variety of Islamic expressions is rising, which gives rise to a new optimism that variations in how Muslims practice Islam can increase social cohesiveness rather than inevitably cause conflict and hostility. This article categorizes prior theories regarding the sense of community, including the perspectives of David W. McMillan and David M. Chavis.